2016
DOI: 10.4067/s0718-34292016005000021
|View full text |Cite
|
Sign up to set email alerts
|

Características de la germinación de Lippiapalmeri (Wats) proveniente de regiones silvestres del desierto de Altar, Sonora, México

Abstract: RESUMENExisten varias especies del género de Lippia nativas e introducidas, que son de gran potencial en zonas áridas del noroeste de México; estas especies presentan bajo porcentaje de germinación debido a la dureza y/o dormancia de la semilla. El objetivo del presente estudio consistió en dilucidar el efecto del ácido giberélico sobre la germinación de la semillas silvestre de Lippia palmeri. Para ello se recolectó la semilla en dos regiones nativas (Puerto del Orégano y Santa Ana, Sonora). Se probaron tres … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This was most likely due to the continual hydration of the media in the FTS, which provided optimal water absorption by seeds compared to the conventional system, in which the media were watered on a regular basis. Fever tea seeds have a stiff seed coat, which limits the amount of water imbibition and consequently the rate of germination [28]. As a result, the FTS's continuous hydration delivered ideal moisture that helped soften the seed coat, allowing the seed to ingest water to hydrate enzymes and membranes, aiding the breakdown and translocation of the stored material.…”
Section: Discussion 1 Influence Of Nursery Growing System and Media T...mentioning
confidence: 99%
See 1 more Smart Citation
“…This was most likely due to the continual hydration of the media in the FTS, which provided optimal water absorption by seeds compared to the conventional system, in which the media were watered on a regular basis. Fever tea seeds have a stiff seed coat, which limits the amount of water imbibition and consequently the rate of germination [28]. As a result, the FTS's continuous hydration delivered ideal moisture that helped soften the seed coat, allowing the seed to ingest water to hydrate enzymes and membranes, aiding the breakdown and translocation of the stored material.…”
Section: Discussion 1 Influence Of Nursery Growing System and Media T...mentioning
confidence: 99%
“…The continual hydration of peat moss in the FTS system and the moisture retention capacity of coco peat in the CON system may have given adequate moisture to soften the seed coat, enhancing the seed's imbibition ability and period. [28] revealed that the hard seed coat was to blame for the poor germination percentages in Lippia species. The difficulty of sand to hold moisture due to its high porosity (64.0) (Table 1) may explain its poor germination percentage in the CON system.…”
Section: Influence Of Nursery Growing System and Media Type On Germin...mentioning
confidence: 99%